Evaluasi Kinerja Mesin CNC Laser Termodifikasi pada Proses Pemotongan Akrilik Presisi - Bukhari Kasim; Azwar Azwar; Mahmud Mahmud; Amalia Harmin; Muhammad Razi; Nurdan Nurdan (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2026)
Computer Numerical Control (CNC) technology innovation has become a core pillar in the manufacturing industry due to its ability to produce high-precision products with optimal time and cost efficiency. This research aims to modify and test the performance of a CNC laser machine, specifically in the cutting process of Polymethyl Methacrylate (PMMA) or acrylic material, to identify the most effective working parameter conditions. The selection of acrylic material is based on its widespread use across various industrial sectors and the need for maximum cutting quality. The research methodology involved two main test series: kerf width analysis and number of passes (through-cutting) analysis. The kerf width testing was conducted by varying the laser focal distance (5mm, 10mm, 20mm) and the combination of power and feeding speed. Meanwhile, the number of passes testing was performed under constant conditions of 100% power and 25mm/min feeding, while varying the acrylic thickness (2mm, 3mm, 5mm) and acrylic color (clear, blue, black). The results show that focal distance is the dominant parameter determining the kerf width range, with 5mm producing the narrowest kerf (0.08mm–0.18mm). As the focal distance increases, the resulting kerf also widens. In terms of cutting efficiency, the Number of passes is directly proportional to material thickness. Intriguingly, clear acrylic was the most difficult to cut (requiring the highest number of passes, up to 4 passes for 5mm), indicating the lowest laser energy absorption under the tested conditions. Conversely, colored acrylic (Black and Blue) showed higher efficiency. This data is essential as a basis for optimizing the performance of CNC Laser machines to produce accurate and efficient acrylic products.